Answer:
x = 6
Step-by-step explanation:
- <em><u>Pull out like factors:
</u></em>
-4x - 13 = -1 • (4x + 13)
- <em><u>Equation at the end of step 2:
</u></em>
-178 - (-5x + -4 • [4x + 13] ) = 0
- <em><u>Pull out like factors:
</u></em>
21x - 126 = 21 • (x - 6)
- <em><u>Equation at the end of step 4:
</u></em>
21 • (x - 6) = 0
x-6 = 0
- <em><u>Add 6 to both sides of the equation:</u></em>
x = 6
B is the right thing 15 squints
Answer:
Definitely Function B
Step-by-step explanation:
Because when you solve the equation it intercepts the X axis
Answer:
B is the correct answer
Kevin is K
Daniel is D
Now: K
K = D + 3
3 years ago:
K - 2 = 4(d - 2)
<h2>YOURE WELCOME, PLEASE MARK AS BRAINLIEST AND FOLLOW ME ❤️❤️</h2>
7.2>0.9(n+8.6)
multiply 0.9 by all in parentheses
7.2> (0.9*n) + (0.9*8.6)
7.2> 0.9n + 7.74
subtract 7.74 from both sides
-0.54> 0.9n
divide both sides by 0.9
-0.6> n
ANSWER: -0.6> n
Hope this helps! :)